The Role of Trust and Contractual Safeguards on Cooperation in Non-equity Alliances - Lui, Steven S.; Ngo, Hang-Yue (Journal of Management, 2004)
Because partners may behave opportunistically in alliances, contractual safeguards or trust between partners are necessary for successful outcomes. However, it remains controversial whether safeguards and trust substitute or complement each other. Drawing on transaction cost theory, this study conceptualizes both contractual safeguards and trust as important control mechanisms in non-equity alliances, and develops a model that relates contractual safeguards and trust to cooperative outcomes. We test our hypotheses with data collected from 233 architect–contractor partnerships in Hong Kong. The results show that the relationship between contractual safeguards and cooperative outcomes depends on both the level and type of trust.